(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2013)
Most of the food industry has cooking processes, where the generated gases are mainly composed of steam. This fluid is sent to the low-pressure environment, therefore it is not used its high energy availability, which stands out its latent heat of condensation. This article aims to design a waste gas recovery, using the turbocharger used in Diesel engines to compress the vapor resulting from the process and recover the wasted heat. In this paper, are determine the parameters of operation of the turbocharger with this new fluid and also determined the operating costs associated with the possible implementation in a brewery. Given this information, we analyze the technical and economic feasibility of using this device in the nation’s food industry.